Warning Indicators in Nepalese Savings Cooperatives: A Longitudinal Financial and Governance Transparency Analysis (The Lumbini Journal of Business and Economics, 2026)
Purpose: This study examines whether publicly available annual reports of Nepalese savings cooperatives contain measurable financial or governance indicators of institutional failure and the efficacy of either by itself or through a combined approach.Methods: A comparative longitudinal design analyzed four years of annual report data (2079-2082 BS) from a sample of seven institutions: two distressed cooperatives, one stable cooperative comparator, one NRB-regulated comparator, and three additional failed cooperatives contributed terminal-year cross-sectional profiles drawn from parliamentary investigation records. A modified CAMEL-based ratio panel covering capital adequacy, asset quality, management efficiency, earnings, and liquidity was used to derive the financial indicator, and a four-dimension Governance Transparency Index (GTI) was scored from annual reports for the governance indicator.Results: Distressed institutions exhibit a consistent deterioration pattern: loan growth acceleration is observed prior to bad loan escalation by one to two years, while nominally stable capital ratios mask expanding provision shortfalls. Related-party disclosure is absent across all distressed cooperatives. The three supplementary failed institutions had severely distressed financial profiles, with capital-to-asset ratios ranging from negative (Ideal Yamuna,-1.30%) to critically low (Gorkha, 2.47%), and liquidity ratios below 1.5% across all three.Conclusion: The combined approach using joint assessment of provisioning adequacy against external audit status was found to separate distressed from stable cooperatives across all observation years, surfacing concealed insolvency that neither financial ratios nor governance disclosure detects in isolation.